The Influence of Information Technology and Use Competency on Company Performance with SIA Effectiveness as a Mediation Variable - Sari, Nita Lukita; Suwandi, Suwandi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The purpose of this study is to analyze the effect of the use of information technology and competence on employee performance by the effectiveness of SIA as a variable mediation The number of respondents in this study was several 280 employees and finance managers. Test the instrument using validity tests and reliability tests. The analysis technique used is SEM (Structural Equation Modelling) AMOS version 21. The results of this study show that: 1) The use of technology has a positive and significant influence on employee performance, 2) Competence has a positive and significant influence on employee performance, 3) The use of technology has a positive and significant influence on employee performance, 4) Competence has a significant influence on employee performance with the effectiveness of SIA.